Nosogogy: A recent concept of patient education and its role in renal patient - Dutta, Pradip Kumar (Journal of Chittagong Medical College Teachers' Association, 2009)
doi: 10.3329/jcmcta.v18i1.3816 Journal of Chittagong Medical College Teachers' Association 2007: 18(1):19-22